The Power of Citation: Feminist Counter-Appropriation of State Discourses in Post-Reform China - Charlie Zhang; Jingxue Zhang (Global Storytelling)
This article presents a comprehensive examination of the new discursive strategy devised and deployed by Chinese pan-feminist communities in response to the pervasive state intrusion, which we call feminist counter-appropriation. These tactics entail adoption and strategic adaptation of the state-sanctioned discourses by feminist netizens to tell their own stories while shielding them from severe punitive measures. Our analysis discerns two types of counter-appropriation practices: deliberate counter-appropriation that involves parodic and satirical redeployment of the party-state’s stigmatizing framing of feminism, and promotional counter-appropriation that uncritically embraces the sanitized version of feminism following the statist and nationalist logic yet creates room for discussion of gender-related and other forms of social inequalities. While acknowledging inherent limitations and susceptibility to manipulation by conservative forces, we argue that these counter-appropriation practices demonstrate the resilience of civil societies in navigating censorship and oppression to subvert the oppressive intentions of party bureaucrats, expose inherent flaws of the official languages, and challenge the entrenched gender inequalities in post-reform China.